INTERNET IMPACT ON THE ACADEMIC PERFORMANCE OF TEENAGERS IN URBAN AREAS - Om Prakash Singh (International Journal of Multidisciplinary Research and Studies, 2021)
At an effort to boost the academic performance of their populations, governments all over the globe have increased the amount of money allocated to the provision of internet and computer access in educational institutions. Although these initiatives were initiated in developed countries such as the United Kingdom, the United States of America (Office of Educational Technology, 2004), and Europe, significant advancements have also been made in developing countries such as Brazil, Nigeria. To paraphrase what Livingstone (2012, page 10) said so eloquently: "...with government policies in recent years to provide internet access for every children and every school, with industry supporting diverse digital education initiatives, and with families gaining internet access at home, much rides on the claim that digital technologies will be as important in the 21st century as the book was in the 19th." Several studies have been conducted to investigate the effect that students' access to the internet has on their academic performance. The first one acknowledges that learning is no longer restricted to just taking place in traditional classrooms (Coleman, 2012), and it investigates the environments in which learning takes place. The authors Furlong and Davis (2012) argue that labelling the use of technology at home as "informal learning" may be misleading. According to the research, the primary location for students' engagement with information and communication technologies (ICTs), especially the internet, is now the home, not the school. Therefore, the authors suggest that environments such as the home, which are becoming more common places for learning to take place, should be considered seriously.